Adaptation in the Age of Media Convergence - Fehrle, Johannes; Schäfke-Zell, Werner (Amsterdam University Press, 2019)
This collection considers new phenomena emerging in a convergence environment from the perspective of adaptation studies. The contributions take the most prominent methods within the field to offer reconsiderations of theoretical concepts and practices in participatory culture, transmedia franchises, and new media adaptations. The authors discuss phenomena ranging from mash-ups of novels and YouTube cover songs to negotiations of authorial control and interpretative authority between media producers and fan communities to perspectives on the fictional and legal framework of brands and franchises. In this fashion, the collection expands the horizons of both adaptation and transmedia studies and provides reassessments of frequently discussed (BBC's Sherlock or the LEGO franchise) and previously largely ignored phenomena (self-censorship in transnational franchises, mash-up novels, or YouTube cover videos).